Influence of emotional stimulus valence on inhibitory control in adults with and without ADHD - Cavallet, Mikael; Chaim-Avancini, Tiffany M.; Biazoli, Claudinei E.; Bazán, Paulo R.; da Silva, Maria Aparecida; Cunha, Paulo Jannuzzi; Miguel, Carmen S.; Busatto, Geraldo F.; Louzã, Mario R.; Gawryszewski, Luiz G. (Experimental brain research, 2016)
Human behavior is influenced both by approach and avoidance automatic reactions to positive and negative stimulus, respectively, but these reactions have not been well studied in attention-deficit/hyperactivity disorder (ADHD) patients. Moreover, studies employing spatial stimulus–response compatibility tasks in ADHD and healthy control (HC) subjects are scarce and inconclusive. The present study investigated inhibitory control and emotional processing in ADHD adults with a modified stimulus–response compatibility task in which spatial and emotional features of affective stimuli had to be processed together to select the correct response. Manual responses to figures of Favorite and Rival soccer team players were measured, and compatible or incompatible responses were chosen according to the soccer team figure. Eighteen HC participants and sixteen ADHD adults performed the task. We found an ordinary spatial compatibility effect for the Favorite soccer team and a reversed one for the Rival team in the ADHD group but not in the HC group. The effects may be due to stronger approach and withdrawal reactions toward the Favorite soccer team and away from the Rival one, respectively, indicating poor inhibitory control for the ADHD group. These results show that differences between ADHD and HC subjects become prominent when response selection involves both emotional and spatial features of the stimulus.